2018
DOI: 10.1111/coa.13229
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high‐grade dysplasia, carcinoma in situ and squamous cell carcinoma in the upper aerodigestive tract: Recommendations for optimal use and interpretation of narrow‐band imaging

Abstract: NBI is a relatively reliable screening method for detecting malignancy. Evaluation based on Ni's classification alone is not sufficient. To optimise NBI photograph quality, we recommend sufficient zooming and prevention of bleeding, blurring and inadequate lighting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Studies published by Piazza et al [29], Nonaka et al [30] and Lin et al [31] prove that NBI is an effective diagnostic method in distinguishing the difference between post-radiation changes and the relapse of a malignant neoplasm. On the other hand, in a study conducted by Zwakenberg et al [32] 96% of patients have shown type IV or V according to the Ni scale despite the fact that histopathological examination has excluded the malignant nature of changes. The authors explain the acquired results with chronic changes occurring in the mucosa after radiochemotherapy treatment.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Studies published by Piazza et al [29], Nonaka et al [30] and Lin et al [31] prove that NBI is an effective diagnostic method in distinguishing the difference between post-radiation changes and the relapse of a malignant neoplasm. On the other hand, in a study conducted by Zwakenberg et al [32] 96% of patients have shown type IV or V according to the Ni scale despite the fact that histopathological examination has excluded the malignant nature of changes. The authors explain the acquired results with chronic changes occurring in the mucosa after radiochemotherapy treatment.…”
Section: Methodsmentioning
confidence: 89%
“…[29] along with Lin et al [31] have adopted the presence of well-limited brownish areas (similar to the ones occurring in type Va according to the Ni scale) as a criterion of malignance. Zwakenberg et al [32] claim that twisted vessels with a regular course, low density and blurred border can be considered as the image of normal vascularisation in post-radiation tissues. Zabrodski et al [33] remind that the macroscopic appearance of the described lesion is also important because the presence of ulcers or necrosis is characteristic for malignant neoplasms.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, NBI improves the resolution of the mucosal surface by limiting the wavelength range of light. A number of meta-analysis studies have shown that NBI performs well in detecting high-grade dysplasia, with sensitivity and specificity reaching 96% and 94%, respectively ( 91 ). At the same time, compared with white light endoscopy, several studies have shown that there is no difference between the two in detecting neoplastic tumors ( 92 , 93 ).…”
Section: Screening Of Ecmentioning
confidence: 99%
“…It is known that blood causes unreliable NBI assessments, due to absorption of the light by hemoglobin. 2,24 Therefore, rigid endoscopy will not be the first choice to determine oropharyngeal tumor extension. We noticed that tumor extension of oropharyngeal tumors was even smaller with NBI compared with WLI evaluation during rigid endoscopy.…”
Section: Tumor Extension and Tumor Classificationmentioning
confidence: 99%
“…32 It is known that NBI endoscopy has a learning curve: training improves the quality of NBI endoscopy, including the interpretation of the images. 24 Ishihara et al described a six-month learning period for evaluation of NBI images. 42 Endoscopists performing the NBI endoscopies in this study were experienced clinicians; however, the results of this study can be translated to less experience clinicians, since we previously found that the intraobserver agreement for less experienced observers improved remarkably when WLI was combined with NBI and less-experienced observers were able to recognize malignant vessel patterns even better.…”
Section: Tumor Extension and Tumor Classificationmentioning
confidence: 99%